Pengaruh Gaya Kepemimpinan Situasional, Kompensasi, dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. AAE Outdoor Indonesia - Febri Antika Sari; Ari Kristiana; Dwi Harini; Nur Khojin (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of situational leadership style, compensation, and job satisfaction on employee performance at PT. AAE Outdoor Indonesia, both partially and simultaneously. The study was motivated by a decline in the number of employees and the importance of improving employee performance to support the achievement of the company's objectives. This research employed a quantitative method with a survey approach. The sample consisted of 93 respondents selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using data quality tests, classical assumption tests, multiple linear regression analysis, partial (t-test), simultaneous (F-test), and the coefficient of determination (R²). The results indicate that situational leadership style (t = 6.397; p = 0.000), compensation (t = 6.485; p = 0.000), and job satisfaction (t = 9.573; p = 0.000) each have a positive and significant effect on employee performance, with job satisfaction being the most dominant variable. Simultaneously, the three variables also have a positive and significant effect on employee performance (F = 31.733; p = 0.000). The Adjusted R² value of 0.501 indicates that 50.1% of the variation in employee performance is explained by these three variables.